Vitamin D₃ levels in the maternal serum, cord blood, and placenta of preeclamptic pregnant women (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Preeclampsia is affected by oxidative stress, a free-radical produced as a by-product of endothelial damage, and antioxidant imbalance, such as vitamin D₃. This study was aimed to compare the vitamin D₃ levels in the placenta, cord blood, and maternal serum between patients with and without preeclampsia. METHODS This cross-sectional study included 86 patients from Cipto Mangunkusumo Hospital and Tangerang District Hospital, in which 47 had preeclampsia (13 early-onset and 16 late-onset preeclampsia cases) and 39 had no preeclampsia. The placenta, cord blood, and maternal serum were taken after labor, then were analyzed according to preeclampsia and non-preeclampsia; furthermore, the preeclampsia group was analyzed in a subgroup of early- and late-onset preeclampsia. This is analyzed with either unpaired t-test, Mann–Whitney U test, or Kruskal–Wallis test. RESULTS The maternal serum, cord blood, and placental tissue vitamin D₃ levels (16.30 [6.20–49.00], 11.80 [3.50–38.60], and 49.00 [22.00–411.00] ng/ml, respectively) of the preeclampsia group were similar to those of the non-preeclampsia group (13.50 [4.80–29.20], 11.70 [1.00–28.80], and 43.40 [11.80–153.00] ng/ml, respectively) (p = 0.459, 0.964, and 0.354, respectively). However, the placental tissue vitamin D₃ levels in early-onset preeclampsia (79.00 [36.00–411.00] ng/ml) were higher than those in late-onset preeclampsia (40.00 [22.00–171.00] ng/ml) (p = 0.006). CONCLUSIONS The vitamin D₃ levels between patients with and without preeclampsia were similar. However, the placental tissue vitamin D₃ levels in early-onset preeclampsia were higher than those in late-onset preeclampsia, possibly because of the different pathophysiology between early- and late-onset preeclampsia.